A critical state model for structural loess considering water content - HOU Le-le (Rock and Soil Mechanics, 2022)
According to the structural evolution behaviors of undisturbed loess with different initial water contents, and based on the theory of critical-state soil mechanics, a critical-state constitutive model is proposed to describe the structural evolution and softening characteristics of undisturbed loess. The model involves stress, initial water content and strain as basic variables. By comparing the isotropic compression curves of remolded and undisturbed loess with different initial water content, the structural parameters and evolution equations of undisturbed loess with different initial water contents have been established. The model adopts the uncorrelated flow rule for plastic strain solver in terms of dilatancy equation. Nine parameters are introduced in the model, which can be calibrated from compression test and conventional triaxial shear test. Compared against the existing experimental data, it is found that this model can not only describe the influence of initial water content on the strength, deformation characteristics and failure mechanism of undisturbed loess structure, but also reasonably predict the hardening and softening characteristics of undisturbed loess. The critical state model of structural loess established in this paper provides a solution for further study of mechanical properties of loess and a theoretical basis for adequate calculation of the collapsibility and deformation of loess foundation.